2012
DOI: 10.1007/s10295-012-1136-7
|View full text |Cite
|
Sign up to set email alerts
|

Effective approach to greatly enhancing selective secretion and expression of three cytoplasmic enzymes in Escherichia coli through synergistic effect of EDTA and lysozyme

Abstract: An effective approach to greatly enhancing the selective secretion and expression of recombinant cytoplasmic enzymes in Escherichia coli was successfully developed through the synergistic effect of ethylenediaminetetraacetate (EDTA) and lysozyme. The method was applied to two endoglucanases (EGs) and an amylase. The optimal culture conditions of temperature and concentration of isopropyl-β-D: -1-thiogalactopyranoside (IPTG) were 23-30 °C and 0.2 mM, respectively, under which the three enzymes could be expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The effect of EDTA-lysozyme combination for secreting xylanase selectively into the extracellular medium at 30 • C after overnight incubation could be attributed to their role in permeabilizing cell membrane [30]. The temperature is another important parameter known to affect the production of soluble recombinant proteins in E. coli [31].…”
Section: Discussionmentioning
confidence: 98%
“…The effect of EDTA-lysozyme combination for secreting xylanase selectively into the extracellular medium at 30 • C after overnight incubation could be attributed to their role in permeabilizing cell membrane [30]. The temperature is another important parameter known to affect the production of soluble recombinant proteins in E. coli [31].…”
Section: Discussionmentioning
confidence: 98%
“…One example of temperature-related expression variability in E. coli is the cellulase from the springtail of Cryptopygus antarcticus , which is best expressed as a soluble protein at 10°C [ 44 ]. Another potential problem is the low secretion of recombinant cellulases in E. coli , which can be improved by ethylenediaminetetraacetic acid (EDTA) treatment [ 45 ] or by the expression of cellulases as OsmY fusion proteins [ 46 ]. OsmY is induced by hyperosmotic stress [ 47 ] and supports the transport of the fusion proteins over the outer membrane [ 46 ], where the fused protein gets cleaved off.…”
Section: Bacterial Expression Systemsmentioning
confidence: 99%
“…Secretion also gives the expressed enzyme greater access to the substrate that is not adequately taken up by cells, such as cellulosic biomass, and opens the path to consolidated bioprocessing (CBP) of cellulose, whereby cost reduction is achieved by combining cellulose hydrolysis and fermentation in a single microorganism. Secretion of recombinant cellodextrinase to the periplasmic space in an E. coli mutant with leaky outer membrane for cellodextrin improved endoglucanase secretion using ethylenediaminetetraacetic acid (EDTA) treatment . Moreover, expression of cellulases as OsmY fusions is one of the few successful examples towards CBP in recombinant E. coli …”
Section: Introductionmentioning
confidence: 99%
“…320 www.soci.org Z Yıldırım, E Çelik Secretion of recombinant cellodextrinase to the periplasmic space in an E. coli mutant with leaky outer membrane for cellodextrin 13 improved endoglucanase secretion using ethylenediaminetetraacetic acid (EDTA) treatment. 14 15 -17 In this study, an endoglucanase (Cel5A) from Fusarium graminearum, previously shown to be a highly active enzyme among 348 cell wall degrading enzymes of plant pathogens, 18 was investigated for extracellular production and compared with periplasmic production. For the extracellular production, Cel5A was fused to YebF, a native E. coli protein that is naturally secreted.…”
Section: Introductionmentioning
confidence: 99%